Volatile oil of Acori tatarinowii rhizoma: potential candidate drugs for mitigating dementia - Bu, Yifan; Li, Songzhe; Ye, Ting; Wang, Yuqing; Song, Mingrong; Chen, Jing (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to elucidate the mitigating effects of the volatile oil of Acori tatarinowii rhizoma (ATR) on dementia, in order to provide a reference for future research and applications of the volatile oil of ATR in the field of dementia.Materials and methodsA search strategy was developed using terms such as “Acori tatarinowii rhizoma,” “Acorus tatarinowii Schott,” “Asarone,” and “Dementia.” The literature search was conducted in PubMed, Web of Science, and Google Scholar, and studies not meeting the inclusion criteria were excluded. This study summarizes the main metabolites, active ingredients, toxicological properties, and pharmacokinetic characteristics of the volatile oil from ATR in mitigating dementia, with a particular focus on its potential mechanisms of action. Furthermore, the study highlights the limitations of existing research and offers insights into future research directions.ResultsThe volatile oil of ATR mitigates dementia through multiple pathways, including reducing abnormal protein aggregation, promoting neurogenesis, inhibiting neuronal apoptosis, regulating neurotransmitters, improving synaptic function, modulating autophagy, countering cellular stress, reducing neuroinflammation, and alleviating vascular risk factors.ConclusionThe multi-pathway pharmacological effects of the volatile oil of ATR are well-aligned with the complex mechanisms of dementia progression, highlighting its significant therapeutic potential for anti-dementia applications. This provides new perspectives for the development of more effective anti-dementia drugs. Nonetheless, further rigorous and high-quality preclinical and clinical investigations are required to address key issues, including the chemical characterization of the volatile oil of ATR, potential synergistic effects among active ingredients, toxicity profiles, and definitive clinical efficacy.